Corrosion-resistant aluminum alloy and preparation process thereof
The 2024 aluminum alloy is processed through hot press forming, solid solution and aging, shot peening and anodizing processes, which solves the problem of insufficient corrosion resistance and achieves the comprehensive performance improvement of high strength, good toughness and excellent corrosion resistance.
Patent Information
- Application Number
- CN202411821284.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The corrosion resistance of 2024 aluminum alloy is weak, and the existing coating protection treatment methods will lead to a decrease in strength when improving corrosion resistance, limiting its application.
The 2024 aluminum alloy is processed using continuous processes of hot press forming, solid solution and aging, shot peening and anodizing. By controlling process parameters such as solid solution temperature, aging temperature, shot peening pressure and anodized electrolyte content, the proportion of second phase particles in the alloy is reduced and corrosion resistance is improved.
It significantly improves the corrosion resistance of aluminum alloys, while maintaining high strength and good toughness. The time for corrosion points to occur in neutral salt spray environments reaches more than 840 hours.
Smart Images

Figure BDA0005183160390000091 
Figure BDA0005183160390000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alloys, and in particular to a corrosion-resistant aluminum alloy and a preparation process thereof. Background Art
[0002] 2024 aluminum alloy is a high-strength hard aluminum, belonging to the Al-Cu-Mg series of aluminum alloys. It can be strengthened by heat treatment, has medium plasticity in the quenched and just-quenched states, is easy to process, has good spot welding performance, and has good thermal conductivity. It has low mass on the basis of high strength, and is the preferred material for lightweight design. It is widely used in aviation, aerospace and other fields, and is mainly used to make various high-load parts and components (but not including stampings and forgings), such as skeleton parts, skins, bulkheads, wing ribs, wing spars, rivets and other working parts.
[0003] With the widespread application of aluminum alloys, people are increasingly studying how to improve their performance, especially the 2024 aluminum alloy, which has average corrosion resistance. Therefore, some people have proposed to use aluminum or zinc-aluminum alloy to coat the 2024 aluminum alloy for protection in order to improve the corrosion resistance of the alloy. However, new problems have emerged in actual use. The 2024 aluminum alloy after coating protection has a problem of reduced strength, which has a certain limiting effect on the application of 2024 aluminum alloy. Therefore, how to improve the weak corrosion resistance of 2024 aluminum alloy without affecting its own advantageous performance has become a major problem at present. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a corrosion-resistant aluminum alloy and a preparation process thereof.
[0005] In a first aspect, the present application provides a process for preparing a corrosion-resistant aluminum alloy, comprising the following steps: S1. Hot pressing: 2024 aluminum alloy powder, Ti powder and graphene are mixed, ball milled, hot pressed and formed, wherein the total weight ratio of the aluminum alloy powder to the titanium powder and the graphene is 100:4, and the weight ratio of the titanium powder to the graphene is (3-4):1; S2, solution treatment and aging: solution treatment at 500-510℃ for 20-24h, water cooling, and then aging treatment at 180-200℃ for 0.5-1h; S3, shot peening: using cast steel shot with a diameter of 0.4-0.5mm, shot peening treatment is carried out under the conditions of shot peening pressure of 0.3-0.5MPa and shot flow rate of 12-13kg / min, and the shot peening coverage is maintained at 100-300%; S4. Anodizing: Anodizing is performed in an electrolyte containing 7-9 g / L DL-malic acid and 40-50 g / L concentrated sulfuric acid to finally obtain a corrosion-resistant aluminum alloy.
[0006] By adopting the above technical scheme, the present application controls parameters such as the solution temperature, aging temperature, diameter of cast steel shot, shot peening pressure, and content of electrolyte used for anodizing, so that the proportion of second phase particles in the alloy that are prone to corrosion is greatly reduced, thereby significantly improving the corrosion resistance of the aluminum alloy. In addition, the present application also performs Ti powder and graphene blending and hot pressing operations on the aluminum alloy before solutionizing. Ti powder can improve the toughness and strength of the aluminum alloy, making up for the defects of reduced strength and toughness of the aluminum alloy caused by shot peening and anodizing. Graphene can form graphene oxide during anodizing, and oxidized graphene appears in the matrix. The bonding strength and dispersion of the graphene oxide with the matrix are much higher than the bonding strength and dispersion of the added graphene oxide with the matrix, which can further improve the corrosion resistance of the corrosion-resistant aluminum alloy finally obtained. At the same time, the present application reduces the roughness of the aluminum alloy surface by strictly controlling the shot peening coverage, and the surface morphology is smoother, which reduces the degree of negative effects such as uneven surface and incomplete formation of corrosion-resistant film on the alloy after anodizing.
[0007] In general, this application processes the 2024 aluminum alloy by adopting a continuous process of hot pressing, solution treatment and aging, shot peening and anodizing. Each step cooperates with each other, and the main process parameters of each step are strictly controlled. Under the premise of ensuring that the aluminum alloy has high strength and good toughness, its corrosion resistance is improved as much as possible. After testing, its yield strength is not less than 685MPa, the ultimate tensile strength is not less than 704MPa, the elongation at break is not less than 9.25%, and the duration of corrosion spots in a neutral salt spray environment is not less than 840h.
[0008] Preferably, in step S2, the temperature of the solution treatment is 505°C, and the temperature of the aging treatment is 190°C.
[0009] By adopting the above technical scheme, the present application strictly controls the temperature of the solution treatment and the temperature of the aging treatment. At this treatment temperature, not only the toughness of the corrosion-resistant aluminum alloy can be maximized, but also its strength and corrosion resistance can be improved to a certain extent, so that the comprehensive performance of the corrosion-resistant aluminum alloy is further optimized.
[0010] Preferably, in step S3, the shot peening coverage is 200%.
[0011] By adopting the above technical scheme, the present application strictly controls the shot peening coverage rate to 200%. At this time, the second phase particles inside the aluminum alloy are almost completely dissolved. More importantly, at this time, the surface roughness of the aluminum alloy reaches the lowest, and the surface morphology is the smoothest. In the subsequent anodizing, it is easier to form a dense and uniform corrosion-resistant film and a closed film, further improving the corrosion resistance of the aluminum alloy.
[0012] Preferably, the sealing in step S4 is specifically as follows: immersing the aluminum alloy taken out from the electrolyte in a sealing solution and standing at a temperature of 25-50°C to obtain a corrosion-resistant aluminum alloy, and the sealing solution is a potassium dichromate solution, a lithium carbonate solution or a nickel sulfate solution.
[0013] By adopting the above technical solution, the present application performs sealing treatment on the oxidized aluminum alloy at a temperature of 25-50°C. Compared with the existing high-temperature sealing environment, the lower temperature sealing environment can make the sealing film on the surface of the aluminum alloy more complete and dense, thereby improving the corrosion resistance of the corrosion-resistant aluminum alloy. If the temperature is higher than 50°C, the above-mentioned sealing film will not be dense enough and complete enough, but if the temperature is lower than 25°C, the viscosity of the sealing liquid will increase, the fluidity will deteriorate, and the sealing reaction rate will be too slow.
[0014] Preferably, the sealing solution is a lithium carbonate solution.
[0015] Preferably, the lithium carbonate concentration of the lithium carbonate solution is 0.03-0.1 mol / L.
[0016] Preferably, the lithium carbonate concentration of the lithium carbonate solution is 0.05 mol / L.
[0017] Preferably, the standing temperature in the enclosure is 30°C.
[0018] By adopting the above-mentioned technical scheme, the present application utilizes lithium carbonate solution as a sealing solution, which can further enhance the corrosion resistance of the corrosion-resistant aluminum alloy compared with potassium dichromate solution and nickel sulfate solution, thereby further reducing its self-corrosion potential, and increasing the duration of the appearance of corrosion points in a neutral salt spray environment to 888 hours. In addition, the concentration of lithium carbonate is strictly controlled. If the concentration is too high, the texture of the sealing film will be uneven, and if the concentration is too low, the density of the sealing film will be insufficient. Subsequently, the present application further controls the temperature during standing on this basis. Experimental data show that when the concentration of lithium carbonate is 0.05 mol / L and the temperature during standing is 30°C, the sealing effect is best, the sealing film on the surface of the aluminum alloy is the densest, and the film formation is the most complete. Finally, the duration of the appearance of corrosion points on the aluminum alloy in a neutral salt spray environment can reach 1032 hours.
[0019] In a second aspect, the present application provides a corrosion-resistant aluminum alloy.
[0020] By adopting the above technical scheme, the corrosion-resistant aluminum alloy of the present application has high strength, certain toughness and excellent corrosion resistance, and its application value in the fields of aviation, aerospace, etc. is further improved. At the same time, the significant improvement in corrosion resistance also broadens its application range and has high practical use value.
[0021] In summary, this application has the following beneficial technical effects: 1. The preparation process of the present application processes 2024 aluminum alloy by adopting a continuous process of hot pressing, solution and aging, shot peening and anodizing. Each step cooperates with each other, and the main process parameters of each step are strictly controlled. Under the premise of ensuring that the aluminum alloy has high strength and high toughness, its corrosion resistance is improved as much as possible. After testing, its yield strength is not less than 685MPa, the ultimate tensile strength is not less than 704MPa, the elongation at break is not less than 9.25%, and the duration of corrosion points in a neutral salt spray environment is not less than 840h; 2. In the preparation process of the present application, lithium carbonate solution is used as a closed solution. Compared with potassium dichromate solution and nickel sulfate solution, the corrosion resistance of the corrosion-resistant aluminum alloy can be further improved, and its self-corrosion potential is further reduced. The duration of the corrosion point appearing in a neutral salt spray environment is increased to 870 hours, and the concentration of lithium carbonate and the temperature at rest are strictly controlled. Finally, the duration of the corrosion point appearing in the neutral salt spray environment of the aluminum alloy can be increased to a maximum of 980 hours; 3. The corrosion-resistant aluminum alloy of the present application has high strength, certain toughness and excellent corrosion resistance, and its application value in the fields of aviation, aerospace, etc. is further improved. At the same time, the significant improvement in corrosion resistance also broadens its application range and has high practical use value. DETAILED DESCRIPTION
[0022] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: The composition of 2024 aluminum alloy is Al-4.43Cu-1.45Mg-0.62Mn-0.12Si-0.11Fe, and the average particle size is 8.7um; Ti powder was purchased from Hebei Teng Bimetallic Materials Co., Ltd. with a specification of 325 mesh; Graphene was purchased from Jianshi Mineral Powder Factory, Lingshou County, with a specification of 2000 mesh; DL-malic acid was purchased from Henan Youchuang Chemical Products Co., Ltd., CAS No. 96-97-6; Concentrated sulfuric acid was purchased from Aladdin Chemical Reagent Co., Ltd. with a concentration of 98 wt%; Nickel sulfate, lithium carbonate, and potassium dichromate were purchased from Aladdin Chemical Reagent Co., Ltd.; Cast steel shot was purchased from Shandong Shengboan Metal Materials Co., Ltd., with a Rockwell hardness of 50HRC; Graphene oxide was purchased from Lingshou County Jianshi Mineral Powder Factory with a specification of 2000 mesh.
[0023] The present application is further described in detail below with reference to examples and comparative examples.
[0024] Example 1.1 A preparation process of a corrosion-resistant aluminum alloy comprises the following steps: S1. Hot pressing: 100 parts by weight of 2024 aluminum alloy powder was mixed with 3 parts of Ti powder and 1 part of graphene, and the mixture was continuously ball-milled at a ball-milling speed of 135 rpm for 8 h. The mixed powder obtained after ball milling was placed in a vacuum hot pressing furnace. The pressure was first increased to 224 MPa and the temperature was increased to 300°C within 5 min. Then the pressure and temperature were maintained for 35 min to obtain a hot pressing block. The hot pressing block was placed in a system with a temperature of 645°C and the vacuum degree was ensured to be less than 10 -2 torr, let it stand for 80 minutes, and then quickly put it into a hydraulic press at a temperature of 250°C, and perform forming treatment under a pressure of 196MPa, and hold the pressure for 30 seconds to obtain the initial alloy ingot with a specification of Φ50mm×10mm; S2, solution treatment and aging: placing the initial alloy ingot obtained in step S1 in a tubular furnace at a temperature of 500° C., solution treatment for 24 hours, water cooling, and then placing it in a tubular furnace at a temperature of 180° C., aging treatment for 1 hour, to obtain a reprocessed alloy ingot; S3, shot peening: using cast steel shot with a diameter of 0.5 mm, the reprocessed alloy ingot obtained in step S2 is shot peened under the conditions of a shot peening pressure of 0.5 MPa, a shot flow rate of 12 kg / min, and a spraying distance of 500 mm, and the shot peening coverage is maintained at 100%; S4, anodizing: the alloy ingot obtained in step S3 is placed in a 50 g / L sodium hydroxide solution at a temperature of 55°C for 1 min, and then taken out. Then, it is treated with a 400 g / L nitric acid solution at room temperature for light treatment. After light treatment, the alloy ingot is taken out and placed in an electrolyte containing 9 g / L DL-malic acid and 40 g / L concentrated sulfuric acid for anodizing. The temperature is set to 25°C, the voltage is 15V, and the time is 20 min. Then, the aluminum alloy is taken out from the electrolyte, immersed in a 0.1 mol / L potassium dichromate solution, and sealed at a temperature of 25°C for 45 min to finally obtain a corrosion-resistant aluminum alloy.
[0025] Example 1.2 A preparation process of a corrosion-resistant aluminum alloy comprises the following steps: S1. Hot pressing: 100 parts by weight of 2024 aluminum alloy powder was mixed with 3.2 parts of Ti powder and 0.8 parts of graphene, and the mixture was continuously ball-milled at a ball-milling speed of 135 rpm for 8 h. The mixed powder obtained after ball milling was placed in a vacuum hot pressing furnace. The pressure was first increased to 224 MPa and the temperature was increased to 300°C within 5 min. Then the pressure and temperature were maintained for 35 min to obtain a hot pressing block. The hot pressing block was placed in a system with a temperature of 645°C and the vacuum degree was ensured to be less than 10 -2torr, let it stand for 80 minutes, and then quickly put it into a hydraulic press at a temperature of 250°C, and perform forming treatment under a pressure of 196MPa, and hold the pressure for 30 seconds to obtain the initial alloy ingot with a specification of Φ50mm×10mm; S2, solution treatment and aging: placing the initial alloy ingot obtained in step S1 in a tubular furnace at a temperature of 510° C., solution treatment for 20 h, water cooling, and then placing it in a tubular furnace at a temperature of 200° C., aging treatment for 0.5 h, to obtain a reprocessed alloy ingot; S3, shot peening: using cast steel shot with a diameter of 0.4 mm, the reprocessed alloy ingot obtained in step S2 is shot peened under the conditions of a shot peening pressure of 0.3 MPa, a shot flow rate of 12 kg / min, and a spraying distance of 500 mm, and the shot peening coverage is maintained at 300%; S4, anodizing: the alloy ingot obtained in step S3 is placed in a 50 g / L sodium hydroxide solution at a temperature of 55°C for washing for 1 min, taken out, and then treated with a 400 g / L nitric acid solution at room temperature. After the light is removed, the alloy ingot is taken out and placed in an electrolyte containing 9 g / L DL-malic acid and 40 g / L concentrated sulfuric acid for anodizing. The temperature is set to 25°C, the voltage is 15V, and the time is 20 min. Then the aluminum alloy is taken out from the electrolyte, immersed in a 0.1 mol / L potassium dichromate solution, and sealed at a temperature of 50°C for 45 min to finally obtain a corrosion-resistant aluminum alloy.
[0026] Example 2 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S2, the temperature of the solution treatment is 505°C, the temperature of the aging treatment is 190°C, and the rest is the same as Example 1.1.
[0027] Example 3 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S3, the shot peening coverage is maintained at 200%, and the rest is the same as Example 1.1.
[0028] Example 4.1 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S4, a sealing treatment is performed at a temperature of 90° C., and the rest is the same as Example 1.1.
[0029] Example 4.2 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S4, a sealing treatment is performed at a temperature of 20° C., and the rest is the same as Example 1.1.
[0030] Example 5.1 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S4, the 0.1 mol / L potassium dichromate solution is replaced with a 0.1 mol / L nickel sulfate solution, and the rest is the same as Example 1.1.
[0031] Example 5.2 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 1.1 in that, in step S4, 0.1 mol / L potassium dichromate solution is replaced by 0.1 mol / L lithium carbonate solution, and the rest is the same as Example 1.1.
[0032] Example 6.1 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 5.2 in that, in step S4, the concentration of the lithium carbonate solution is 0.03 mol / L, and the rest is the same as Example 5.2.
[0033] Example 6.2 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 5.2 in that, in step S4, the concentration of the lithium carbonate solution is 0.05 mol / L, and the rest is the same as Example 5.2.
[0034] Example 6.3 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 5.2 in that, in step S4, the concentration of the lithium carbonate solution is 0.07 mol / L, and the rest is the same as Example 5.2.
[0035] Example 6.4 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 5.2 in that, in step S4, the concentration of the lithium carbonate solution is 0.09 mol / L, and the rest is the same as Example 5.2.
[0036] Example 7.1 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 6.1 in that, in step S4, the temperature during the sealing treatment is 30°C, and the rest is the same as Example 6.1.
[0037] Example 7.2 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 6.2 in that, in step S4, the temperature during the sealing treatment is 35°C, and the rest is the same as Example 6.2.
[0038] Example 7.3 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 6.2 in that, in step S4, the temperature during the sealing treatment is 40°C, and the rest is the same as Example 6.2.
[0039] Example 7.4 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 6.2 in that, in step S4, the temperature during the sealing treatment is 45°C, and the rest is the same as Example 6.2.
[0040] Example 7.5 A preparation process of a corrosion-resistant aluminum alloy, which is different from Example 6.2 in that, in step S4, the temperature during the sealing treatment is 50°C, and the rest is the same as Example 6.2.
[0041] Comparative Example 1.1 The difference from Example 1.1 is that step S1 is removed, and the rest is the same as Example 1.1, specifically: S1. Solution treatment and aging: placing an alloy ingot with a specification of Φ50mm×10mm in a tubular furnace at a temperature of 500°C, solution treatment for 24h, water cooling, and then placing it in a tubular furnace at a temperature of 180°C, aging treatment for 1h, to obtain a reprocessed alloy ingot; S2, shot peening: using cast steel shot with a diameter of 0.5 mm, the reprocessed alloy ingot obtained in step S2 is shot peened under the conditions of a shot peening pressure of 0.5 MPa, a shot flow rate of 12 kg / min, and a spraying distance of 500 mm, and the shot peening coverage is maintained at 100%; S3, anodizing: the alloy ingot obtained in step S3 is placed in a 50 g / L sodium hydroxide solution at a temperature of 55°C for washing for 1 min, taken out, and then treated with a 400 g / L nitric acid solution at room temperature. After the light is removed, the alloy ingot is taken out and placed in an electrolyte containing 9 g / L DL-malic acid and 40 g / L concentrated sulfuric acid for anodizing. The temperature is set to 25°C, the voltage is 15V, and the time is 20 min. Then the aluminum alloy is taken out from the electrolyte, immersed in a 0.1 mol / L potassium dichromate solution, and sealed at a temperature of 25°C for 45 min to finally obtain a corrosion-resistant aluminum alloy.
[0042] Comparative Example 1.2 The difference from Example 1.1 is that the Ti powder and graphene in step S1 are all replaced by graphene, and the rest is the same as Example 1.1.
[0043] Comparative Example 1.3 The difference from Example 1.1 is that the Ti powder and graphene in step S1 are all replaced by Ti powder, and the rest is the same as Example 1.1.
[0044] Comparative Example 1.4 The difference from Example 1.1 is that all the graphene in step S1 is replaced by graphene oxide, and the rest is the same as Example 1.1.
[0045] Comparative Example 1.5 The difference from Example 1.1 is that the Ti powder and graphene in step S1 are all replaced by graphene oxide, step S3 is removed, and the rest is the same as Example 1.1.
[0046] Comparative Example 2.1 The difference from Example 1.1 is that in step S2, the temperature of the solution treatment is 550°C, and the temperature of the aging treatment is 220°C. The rest is the same as Example 1.1.
[0047] Comparative Example 2.2 The difference from Example 1.1 is that in step S2, the temperature of the solution treatment is 450°C, and the temperature of the aging treatment is 150°C. The rest is the same as Example 1.1.
[0048] Comparative Example 3 The difference from Example 1.1 is that anodizing is performed first and then shot peening is performed, specifically: S1. Hot pressing: 100 parts by weight of 2024 aluminum alloy powder, 3 parts of Ti powder and 1 part of graphene were mixed and ball-milled continuously at a ball-milling speed of 135 rpm for 8 hours. The mixed powder obtained after ball milling was placed in a vacuum hot pressing furnace. The pressure was first increased to 224 MPa and the temperature was increased to 300°C within 5 minutes. Then, the pressure and temperature were maintained for 35 minutes to obtain a hot pressing block. The hot pressing block was placed in a system with a temperature of 645°C and the vacuum degree was ensured to be less than 10 -2 torr, let it stand for 80 minutes, and then quickly put it into a hydraulic press at a temperature of 250°C, and perform forming treatment under a pressure of 196MPa, and hold the pressure for 30 seconds to obtain the initial alloy ingot with a specification of Φ50mm×10mm; S2, solution treatment and aging: placing the initial alloy ingot obtained in step S1 in a tubular furnace at a temperature of 500° C., solution treatment for 24 hours, water cooling, and then placing it in a tubular furnace at a temperature of 180° C., aging treatment for 1 hour, to obtain a reprocessed alloy ingot; S3, anodizing: the reprocessed alloy ingot obtained in step S2 is placed in a 50 g / L sodium hydroxide solution at a temperature of 55°C for 1 min, taken out, and then treated with a 400 g / L nitric acid solution at room temperature. After the light is removed, the alloy ingot is taken out and placed in an electrolyte containing 9 g / L DL-malic acid and 40 g / L concentrated sulfuric acid for anodizing. The temperature is set to 25°C, the voltage is 15V, and the time is 20 min. Then, the aluminum alloy is taken out from the electrolyte, immersed in a 0.1 mol / L potassium dichromate solution, and sealed at a temperature of 25°C for 45 min. S4. Shot peening: Use cast steel shots with a diameter of 0.5 mm to shot peen the alloy ingot obtained in step S3 under the conditions of a shot peening pressure of 0.5 MPa, a shot flow rate of 12 kg / min, and a spraying distance of 500 mm, and keep the shot peening coverage rate at 100%, and finally obtain a corrosion-resistant aluminum alloy.
[0049] Comparative Example 4.1 The difference from Example 1.1 is that in step S3, the shot peening pressure is 0.2 MPa, and the rest is the same as Example 1.1.
[0050] Comparative Example 4.2 The difference from Example 1.1 is that in step S3, the shot peening pressure is 0.6 MPa, and the rest is the same as Example 1.1.
[0051] Comparative Example 4.3 The difference from Example 1.1 is that in step S3, the shot flow rate is 10 kg / min, and the rest is the same as Example 1.1.
[0052] Comparative Example 4.4 The difference from Example 1.1 is that in step S3, the shot flow rate is 15 kg / min, and the rest is the same as Example 1.1.
[0053] Comparative Example 4.5 The difference from Example 1.1 is that in step S3, the shot peening coverage is maintained at 400%, and the rest is the same as Example 1.1.
[0054] Comparative Example 5.1 The difference from Example 1.1 is that in step S4, the electrolyte contains only 49 g / L of DL-malic acid, and the rest is the same as Example 1.1.
[0055] Comparative Example 5.2 The difference from Example 1.1 is that in step S4, the electrolyte contains only 49 g / L of concentrated sulfuric acid, and the rest is the same as Example 1.1.
[0056] Performance Testing The 2024 aluminum alloy powder (Al-4.43Cu-1.45Mg-0.62Mn-0.12Si-0.11Fe) was melted and cast into alloy ingots with a specification of Φ50mm×10mm, and used as a blank control group for subsequent experiments: 1. Neutral salt spray test: According to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test" neutral salt spray (NSS) test, using 50g / L NaCl solution with pH = 6.5-7.2, the corrosion-resistant aluminum alloy samples obtained in the blank group, the embodiment and the comparative example were placed with the test surface facing up and at 30° in the vertical direction, the set temperature was 35°C, and the test was repeated every 80cm. 2 The sedimentation rate of the area is 1-2 mL / h. The surface morphology of the sample is observed every 24 hours, and the duration of the corrosion point appearance is recorded; 2. Mechanical properties test: According to GB / T 228-2010 “Metal Tensile Test Methods”, the corrosion-resistant aluminum alloys of the blank group, the embodiments and the comparative examples were processed into standard tensile specimens, and stretched at room temperature on a DNS500 electronic tensile testing machine at a stretching rate of 2 mm / min. The yield strength, ultimate tensile strength and elongation at break were recorded.
[0057] Table 1 Performance test table Data Analysis: As can be seen from Table 1, the corrosion-resistant aluminum alloy obtained by the preparation process of Examples 1.1-1.2 has a corrosion point appearance time of 840h in the neutral salt spray test, a yield strength of 685-686MPa, an ultimate tensile strength of 704-708MPa, and an elongation at break of 9.25-9.27%, which proves that the present application treats the 2024 aluminum alloy by adopting a continuous process of hot pressing, solutionizing and aging, shot peening and anodizing, and each step cooperates with each other. At the same time, the main process parameters of each step are strictly controlled, and the corrosion resistance of the aluminum alloy is improved as much as possible under the premise of ensuring that the aluminum alloy has high strength and good toughness; The corrosion point appearance time, yield strength, ultimate tensile strength and elongation at break of the corrosion-resistant aluminum alloy obtained by the preparation process of Example 2 are significantly higher than those of Example 1.1, which proves that the present application can maximize the toughness of the corrosion-resistant aluminum alloy by strictly controlling the temperature of the solid solution treatment and the temperature of the aging treatment. At this treatment temperature, the strength and corrosion resistance of the corrosion-resistant aluminum alloy are also improved to a certain extent, so that the comprehensive performance of the corrosion-resistant aluminum alloy is further optimized; The corrosion point appearance time of the corrosion-resistant aluminum alloy obtained by the preparation process of Example 3 is much longer than that of Example 1.1, which proves that the present application strictly controls the shot peening coverage rate to 200%, so that the second phase particles inside the aluminum alloy are almost completely dissolved at this time. More importantly, the surface roughness of the aluminum alloy reaches the lowest at this time, and the surface morphology is the smoothest. It is easier to form a dense and uniform corrosion-resistant film and a closed film in the subsequent anodizing, which further improves the corrosion resistance of the aluminum alloy. The difference between Example 4.1-4.2 and Example 1.1 is that the temperature of the sealing treatment is changed, and the corrosion point appearance time of the corrosion-resistant aluminum alloy obtained by the preparation process of Example 4.1-4.2 is lower than that of Example 1.1, which proves that the present application performs sealing treatment on the oxidized aluminum alloy at a temperature of 25-50°C. Compared with the existing high-temperature sealing environment, the lower temperature sealing environment can make the sealing film on the surface of the aluminum alloy more complete and dense, thereby improving the corrosion resistance of the corrosion-resistant aluminum alloy. If the temperature is higher than 50°C, the above-mentioned sealing film will be not dense enough and complete enough, but if the temperature is lower than 25°C, the viscosity of the sealing liquid will increase, the fluidity will deteriorate, and the sealing reaction rate will be too slow. The difference between Examples 5.1-5.2 and Example 1.1 is that different types of sealing solutions are replaced, and the time for the corrosion point to appear in the corrosion-resistant aluminum alloy obtained by the preparation process of Example 5.2 is much longer than that in Example 1.1 and Example 5.1, which proves that the present application uses lithium carbonate solution as a sealing solution, which can further improve the corrosion resistance of the corrosion-resistant aluminum alloy compared with potassium dichromate solution and nickel sulfate solution, and further reduce its self-corrosion potential, and the time for the corrosion point to appear in a neutral salt spray environment is increased to 888h; The difference between Examples 6.1-6.4 and Example 1.1 is that the concentration of the lithium carbonate solution is changed, wherein the corrosion point appearance time of the corrosion-resistant aluminum alloy obtained by the preparation process of Example 6.2 is much longer than that of Example 1.1 and Example 6.1, and Examples 6.3-6.4. On this basis, the present application further adjusts the temperature of the sealing treatment in Examples 7.1-7.5, and obtains that the corrosion point appearance time of the corrosion-resistant aluminum alloy obtained by the preparation process of Example 7.1 is the longest, which can reach 1032h, proving that the present application strictly controls the concentration of lithium carbonate, and further controls the temperature during standing on this basis, so that the closed film on the surface of the aluminum alloy has the highest density, the film formation is the most complete, and the corrosion resistance of the aluminum alloy reaches the best; The difference between Comparative Example 1.1 and Example 1.1 is that step S1 is removed. It is found that the corrosion point time, yield strength, ultimate tensile strength and elongation at break of the aluminum alloy are greatly reduced, which proves that the present application ensures that the aluminum alloy has high strength, good toughness and excellent corrosion resistance by mixing 2024 aluminum alloy powder with Ti powder and graphene and hot pressing them. The difference between Comparative Examples 1.2-1.3 and Example 1.1 is that the Ti powder and graphene in step S1 are removed respectively. It is found that the corrosion point time, yield strength, ultimate tensile strength and elongation at break of the aluminum alloy are greatly reduced, which proves that the present application can ensure that the aluminum alloy has high strength, good toughness and excellent corrosion resistance through the synergistic effect between Ti powder and graphene; The difference between Comparative Example 1.4 and Example 1.1 is that graphene is replaced with graphene oxide, and the difference between Comparative Example 1.5 and Example 1.1 is that both Ti powder and graphene are replaced with graphene oxide, and the step of anodizing is removed. Finally, the time for the corrosion point to appear in Comparative Examples 1.4-1.5 is much shorter than that in Example 1.1, proving that the present application utilizes the oxidation of graphene in the matrix to form graphene oxide, and its bonding strength and dispersion with the matrix are much higher than those of the externally added graphene oxide with the matrix, which can further improve the corrosion resistance of the corrosion-resistant aluminum alloy finally obtained, and at the same time, anodizing can make the alloy The proportion of second phase particles that are prone to corrosion in the aluminum alloy is greatly reduced, thereby significantly improving the corrosion resistance of the aluminum alloy; the difference between comparative examples 2.1-2.2 and embodiment 1.1 is that the temperature of solid solution and aging is adjusted, and it is found that the corrosion point time, yield strength, ultimate tensile strength and elongation at break of the aluminum alloy are reduced at this time, which proves that the present application can not only maximize the toughness of the corrosion-resistant aluminum alloy by strictly controlling the temperature of solid solution treatment and the temperature of aging treatment at this treatment temperature, but also improve its strength and corrosion resistance to a certain extent, so that the comprehensive performance of the corrosion-resistant aluminum alloy is further optimized; The difference between Comparative Example 3 and Example 1.1 is that anodizing is performed first and then shot peening is performed. It is found that the time for the appearance of corrosion points of the aluminum alloy is greatly reduced, which proves that the preparation processes of the present application cooperate with each other and can improve the corrosion resistance of the aluminum alloy as much as possible. The difference between Comparative Examples 4.1-5.2 and Example 1.1 is that the process parameters in step S3 and step S4 are adjusted. It is found that the yield strength, ultimate tensile strength and elongation at break of the aluminum alloy are reduced at this time. This proves that the present application improves the corrosion resistance of the aluminum alloy as much as possible while ensuring that the aluminum alloy has high strength and good toughness by strictly controlling the main process parameters of each step.
[0058] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A process for preparing a corrosion-resistant aluminum alloy, characterized in that: The following steps are involved: S1. Hot pressing: 2024 aluminum alloy powder, Ti powder and graphene are mixed, ball milled, hot pressed and formed, wherein the total weight ratio of the aluminum alloy powder to the titanium powder and the graphene is 100:4, and the weight ratio of the titanium powder to the graphene is (3-4):1; S2, solution treatment and aging: solution treatment at 500-510℃ for 20-24h, water cooling, and then aging treatment at 180-200℃ for 0.5-1h; S3, Shot peening: Use cast steel shot with a diameter of 0.4-0.5mm, and perform shot peening at a shot peening pressure of 0.3-0.5MPa and a shot flow rate of 12-13kg / min, and maintain a shot peening coverage of 100-300%; S4. Anodizing: Anodizing is performed in an electrolyte containing 7-9 g / L DL-malic acid and 40-50 g / L concentrated sulfuric acid, and sealing is performed to finally obtain a corrosion-resistant aluminum alloy.
2. The process for preparing a corrosion-resistant aluminum alloy according to claim 1, characterized in that: In the step S2, the temperature of the solution treatment is 505°C, and the temperature of the aging treatment is 190°C.
3. The process for preparing a corrosion-resistant aluminum alloy according to claim 1, characterized in that: In step S3, the shot peening coverage is 200%.
4. The process for preparing a corrosion-resistant aluminum alloy according to claim 1, characterized in that: The closure in step S4 is specifically: The aluminum alloy taken out from the electrolyte is immersed in a sealing solution and allowed to stand at a temperature of 25-50° C. to obtain a corrosion-resistant aluminum alloy. The sealing solution is a potassium dichromate solution, a lithium carbonate solution or a nickel sulfate solution.
5. The process for preparing a corrosion-resistant aluminum alloy according to claim 4, characterized in that: The sealing solution is a lithium carbonate solution.
6. The process for preparing a corrosion-resistant aluminum alloy according to claim 5, characterized in that: The lithium carbonate concentration of the lithium carbonate solution is 0.03-0.1 mol / L.
7. The process for preparing a corrosion-resistant aluminum alloy according to claim 6, characterized in that: The lithium carbonate concentration of the lithium carbonate solution is 0.05 mol / L.
8. The process for preparing a corrosion-resistant aluminum alloy according to claim 7, characterized in that: The standing temperature in the enclosure was 30°C.
9. A corrosion-resistant aluminum alloy obtained by the preparation process according to any one of claims 1 to 8.